Empowered or Impoverished: The Impact of Panic Buttons on Domestic Violence - Semih Tumen; Hakan Ulucan (Institute of Labor Economics (IZA), 2019)
This paper estimates the causal effect of a targeted panic button programâ exteuro“implemented in two Turkish provinces between 2012 and 2016â exteuro“on domestic violence against women. Diff-in-diff and synthetic control estimates suggest that the program notably increased physical domestic violence against women both at the extensive and intensive margins. Specifically, we find that the likelihood of physical domestic violence against women in the treated provinces increased by more than 5 percentage points relative to the control provinces, and the number of domestic physical violence incidents against women increased by around 10 percent. The increase comes almost entirely from the increase in violence against less-educated women with high fertility. We show that employment rates and economic independence indicators have improved for those women in the treated provinces, which suggests that the program have economically empowered and encouraged vulnerable women. However, partners/husbands of those women started using more physical violence in response to female empowerment. Our results are consistent with the "male backlash" theories and a class of non-cooperative models incorporating domestic violence as a vehicle/instrument for enhancing bargaining power, but inconsistent with the models predicting that economic empowerment of women reduces domestic violence against them by balancing bargaining power within the household. We also develop a method to understand whether the increase is attributable to actual or self-reported violence. We conclude that the estimates are entirely driven by the increase in actual rather than self-reported violence.
Keywords: J12; J16; K36; 330; female empowerment; male backlash; panic button; domestic violence; bargaining